Asymptomatic people with well-controlled HIV do not have abnormal left ventricular global longitudinal strain - Hoy, Jennifer F.; Lee, Sue J.; Trevillyan, Janine M.; Dewar, Elizabeth M.; Roney, Janine; Dart, Anthony; Yang, Yan (Frontiers in Cardiovascular Medicine, 2023)
Previous studies have reported impairment in systolic and diastolic function in people with HIV (PWHIV). Our aim was to determine if echocardiographically-measured left ventricular (LV) global longitudinal strain (GLS) is abnormal in asymptomatic PWHIV.A cross-sectional study of PWHIV (n=98, 89% male, median age 53 years) and HIV-negative people (n=50, median age 53 years) without known cardiovascular disease were recruited from a single centre. All participants completed a health/lifestyle questionnaire, provided a fasting blood sample and underwent a comprehensive echocardiogram for assessment of diastolic and systolic LV function, including measurement of GLS.All PWHIV were receiving antiretroviral therapy (ART) for a median of 12 years (IQR 6.9, 22.4), the majority with good virological control (86% suppressed) and without immunological compromise (median CD4 598 cells/µL, IQR 388, 841). Compared with controls of similar age and gender, there was no difference in GLS (mean GLS -20.3% (SD 2.5%) versus -21.0% (SD 2.5%), p=0.14) or left 2 This is a provisional file, not the final typeset article ventricular ejection fractions (65.3% (SD 6.3) versus 64.8% (SD 4.8), p=0.62). Following adjustment for covariates (gender, heart rate, systolic and diastolic blood pressure, fasting glucose), the difference in GLS remained non-significant. There were no differences in LV diastolic function between the groups. Exposure to at least one mitochondrially-toxic ART drug (didanosine, stavudine, zidovudine or zalcitabine) was not associated with impairment of LV systolic function.No clinically significant impairment of myocardial systolic function, as measured by LV GLS, was detected in this predominantly Caucasian male population of PWHIV on long term ART, and with no history of cardiovascular disease.